Sistem Penjaminan Mutu Eksternal (SPME) - Kastaji, Kustiono; Akhyak, Akhyak; Muhajir, As'aril; Efendi, Nur (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of writing this work is to analyze the form of an external quality assurance system (SPME). The library research method for studying the External Quality Assurance System (SPME) in Indonesian higher education involves collecting, analyzing and interpreting secondary data from various trusted sources such as books, scientific journals, articles, reports and official documents. The steps include identifying and selecting relevant literature, reviewing the literature to understand SPME concepts and practices, and organizing and synthesizing data to provide a comprehensive picture of SPME. It is hoped that the results of this research can be used as a basis for developing strategies to improve the quality of higher education in Indonesia. The result of this work is that the implementation of the External Quality Assurance System (SPME) in Indonesian higher education institutions faces various obstacles such as limited human resources, facilities and infrastructure, as well as financial constraints, which hinder the effectiveness of quality assurance. To overcome these obstacles, increased resource support, technological infrastructure and ongoing professional training are needed. Collaboration between universities, accreditation institutions, government and industry is very important to improve the quality of higher education. With the right strategy, the quality of higher education in Indonesia can be improved, producing graduates who are competent and ready to compete on the global stage.